Features of liver damage in patients with coronavirus disease (COVID-19) with pneumonia in relation to indicators of inflammation taking into account oxygen dependence - Riabokon, O. V.; Kuliesh, I. O. (Pathologia, 2024)
Aim. The purpose of the work is to analyze the biochemical indicators of liver function in relation to indicators of inflammation in patients with coronavirus disease (COVID-19) with pneumonia, taking into account the development of oxygen dependence. Material and methods. 123 patients with COVID-19 with pneumonia were examined. The diagnosis was confirmed by isolation of RNA-SARS-CoV-2 from the nasopharyngeal mucus by polymerase chain reaction. The presence of pneumonia in all patients was confirmed by X-ray or computer tomography of the chest organs. The patients were divided into groups: I group – 32 patients with a moderately severe course without oxygen dependence; II group – 91 patients with a severe course with oxygen dependence. Exclusion criteria from the research were: the presence of infection with hepatotropic viruses and the presence of previously diagnosed other chronic liver diseases. Statistical data processing was carried out in the program Statistica for Windows 13 (StatSoft Inc., No. JPZ804I382130ARCN10-J). Results. In 45.5 % of patients with COVID-19 with pneumonia at the time of hospitalization by 9.0 [7.0; 12.0] days of the disease, liver damage with the development of cytolytic syndrome was confirmed. The frequency of liver damage in patients with COVID-19 with pneumonia increased with the appearance of oxygen dependence (25.0 % vs. 52.7 %, p = 0.007). Biochemical signs of the syndrome of intrahepatic cholestasis were weakly expressed, with the appearance of oxygen dependence, they were characterized by an increase the number of patients with an elevated level of gammaglutamyltranspeptidase (59.7 % vs. 24.0 %, p = 0.002) in the absence of statistically significant changes in the median indicators activity of gammaglutamyltranspeptidase and alkaline phosphatase (p > 0.05). The relationship between liver damage and the development of oxygen dependence in patients with COVID-19 with pneumonia is confirmed by the correlation between the activity index of alanine aminotransferase (ALT) and the oxygen saturation index (r = -0.31, p < 0.05). In patients with COVID-19 with pneumonia in the dynamics after a week in presence of oxygen dependence, a higher level of activity of ALT remained (p < 0.05) and the frequency of detection of increased activity of ALT remained higher (62.6 % vs. 37.5 %, χ2 = 6.07, p = 0.01), the activity of aspartate aminotransferase is higher (p < 0.05), compared to patients with COVID-19 with pneumonia without oxygen dependence. A higher frequency of liver damage in patients with COVID-19 with pneumonia in presence of oxygen dependence is combined with more pronounced changes in acute inflammatory parameters, namely a higher level of C-reactive protein (CRP) in blood serum (p < 0.01), more frequent (p = 0.001) and more pronounced (p = 0.004) absolute lymphopenia, a higher level of absolute neutrophilia (p = 0.03) and, accordingly, a higher coefficient of N/L ratio (p = 0.0001). The oxygen saturation indicator correlates with the indicators: CRP (r = -0.37, p < 0.05), relative (r = +0.36, p < 0.05) and absolute (r = +0.23, p < 0.05) number of lymphocytes, the absolute number of neutrophils (r = -0.32, p < 0.05) and the ratio of N/L (r = -0.42, p < 0.05). Conclusions. Liver damage with the development of cytolytic syndrome was established in 45.5 % of patients with COVID-19 with pneumonia at the time of hospitalization. The dependence of the frequency of liver damage with the appearance of oxygen dependence, as well as the relationship with acute inflammatory indicators, was demonstrated.